Upaya Peningkatan Skill Master of Ceremony pada Siswa Dengan Penerapan Self-Efficacy dan Impression Management - Nurin Niswah; Aura Hilda Haryono; Apri Arisandi (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2023)
Speaking is one of the skills possessed by all people naturally. To have good communication skills, it is required to have consistent understanding, technique, and practice. One of the public speaking skills is becoming a master of ceremony (MC). A master of ceremony sometimes still feels nervous which is normal because it is a part of internal conflicts. For this reason, self-efficacy or the confidence of a presenter is needed to reduce this nervous. In addition, the confidence possessed by the presenter must also be supported by impression management, which aims to gain the sympathy or attention of the audiences. The writers and their friends organize the socialization and training of master of ceremony during their kuliah kerja nyata, or voluntary, at SMPN Satu Atap in Blumbungan Village, Pamekasan. The aims of this activity are to implement one of programs proposed by the group 41 and increase the soft skills of Satu Atap Junior High School students, so they can prepare themselves when they are appointed to become a presenter in an event. The writers hope that students can become professional presenters and have good public speaking skills. Furthermore, the writers hope that this activity will make students realize how self-efficacy and impression management are important in public speaking, especially in being a master of ceremony